Protein nanoparticles induce the activation of voltage-dependent non-selective ion channels to modulate biological osmotic pressure in cytotoxic cerebral edema - Fan, Wei; Liu, Liming; Yin, Yuxuan; Zhang, Jiayi; Qiu, Zhaoshun; Guo, Jun; Li, Guangming (Frontiers in Pharmacology, 2024)
Introduction: Cytotoxic cerebral edema is a serious complication associated with cerebral ischemic stroke and is widely treated using the hypertonic dehydrant. Here, we propose, for the first time, the decrease of intracellular osmosis as a treatment strategy for alleviating cytotoxic cerebral edema.We established a fluorescence resonance energy transfer-based intermediate filament tension probe for the study and in situ evaluation of osmotic gradients, which were examined in real-time in living cells from primary cultures as well as cell lines.The MCAO rat model was used to confirm our therapy of cerebral edema.: Depolymerization of microfilaments/microtubules and the production of NLRP3 inflammasome resulted in an abundance of protein nanoparticles (PNs) in the glutamate-induced swelling of astrocytes. PNs induced changes in membrane potential and intracellular second messengers, thereby contributing to hyper-osmosis and the resultant astrocyte swelling via the activation of voltage-dependent nonselective ion channels. Therefore, multiple inhibitors of PNs, sodium and chloride ion channels were screened as compound combinations, based on a decrease in cell osmosis and astrocyte swelling, which was followed by further confirmation of the effectiveness of the compound combination against alleviated cerebral edema after ischemia. Discussion: The present study proposes new pathological mechanisms underlying 'electrophysiology-biochemical signal-osmotic tension', which are responsible for cascade regulation in cerebral edema. It also explores various compound combinations as a potential treatment strategy for cerebral edema, which act by multi-targeting intracellular PNs and voltage-dependent nonselective ion flux to reduce astrocyte osmosis.